Pharmacological Potential Of Moringa Oleifera Silver Nanoparticles Targeting Angiogenesis And Colorectal Cancer Cell Lines Inhibition - Al-Shalabi, Rolla Ziyad Mustafa (2025)
Anti-angiogenic agents from natural sources are promising candidates for cancer therapy, especially when formulated through nanotechnology approaches, which are considered a modern and promising field for treating various hard to control cancers. This study aims to evaluate the potential of M. oleifera silver nanoparticles (MOAgNPs) in inhibiting and disrupting neovascularisation in existing vessels (angiogenesis).